Verbal Processes In The Covid-19 News Discourses: An Analysis Of ‘aswaqpress.com’ Coverage On Malaysia - Muhammad Marwan Ismail; Farah Nadia Harun; Wan Moharani Mohammad; Nurhasma Muhammad Saad; Sulaiman Ismail (Penerbit KUIS, 2024)
Indexed by MyCite